Populasi Telur Nyamuk Aedes sp. Pada Ovitrap yang Diberi Fermentasi Gula sebagai Atraktan Alami di Lingkungan Kampus FMIPA Universitas Lampung - Sekar Pratiwi; Emantis Rosa; Priyambodo Priyambodo; Tugiyono Tugiyono (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
Diseases transmitted by mosquito especially Aedes sp. there’s still happens in many areas of both city and village in Indonesia, until reducing Aedes sp. requires controlled effort. Attractant is a compound that can effect the behavior of mosquito even to decrease the population of mosquito directly. Sugar fermentation can be a natural attractant, this solution can produce carbon dioxide compound that can be a attract for mosquito, until mosquitoes are attracted to ovitrap. The purposes of this research was to determined the sugar fermentation to total of Aedes sp. eggs at ovitrap. The research design used is a Complete Random Design (CRD) with 5 repeated. Analysis of data using Analysis of Variance (ANOVA) and if there are the significant differences of treatment then test continued with BNT test signification levels α = 5%. The result is indicate that fermentation formula P1 (50 gr brown sugar+ 1 g yeast) found up to 15 mosquitos eggs at ovitrap with a percentage of 50% more than any other formula, ANOVA test indicate that the value of p<0,05 that’s mean there is none significant differences between the treatment. Key words: Aedes sp.; attractant; sugar fermentation